Sustainable Potential of Tuna Fishery Around the Waters of North Sulawesi Province Based on Data from the Bitung Ocean Fisheries Port (PPS) - Donald H. Simanjuntak; Lawrence J. L. Lumingas; Joudy R. R. Sangari (Sam Ratulangi University, 2021)
This research was conducted in the city of Bitung, North Sulawesi Province with activities centered on the Bitung Ocean Fisheries Port (PPS), which began from mid March to April 2019. The fishing activities studied are using the fishing areas around the waters of North Sulawesi Province namely the Sulawesi Sea and The Maluku Sea which are included in WPP 715 and 716 based on tuna catch landed data on PPS Bitung. The purpose of this study was to analyze the value of sustainable potential by looking at the level of utilization and Maximum Sustainable Yield (MSY) of tuna in the waters around North Sulawesi Province based on a surplus production model approach (Schaefer Model). This research is expected to be used as a consideration in the management of tuna stocks around the waters of North Sulawesi Province, and can be used as a basis for further research. This study uses a secondary data collection method in the form of fishery statistics documents. The data used are data from tuna fishing and fishing (effort), from 2014 to 2018 (5 years). The results showed that the sustainable potential of tuna fisheries around the waters of North Sulawesi Province based on North Sulawesi PPS data indicated that, the sustainable potential value of tuna that could be caught was 14,173.51 tons / year which is counted as 80% of the value of tuna resources around the waters of North Sulawesi Province. PPS Bitung data which amounted to 17,716.15 tons / year for Hmsy, 1,200.15 trips / year for Emsy, with an average CPUE value of 2014-2018 of 19 tons / trip. The level of tuna utilization around the waters of North Sulawesi Province is based on data from PPS Bitung in 2014, 2017 and 2018 which indicate that there were indications of overfishing with the largest utilization rate in 2014 which reached a value of 155.09%.Keywords: tuna, Bitung, Bitung PPS, sustainable potential, MSY. ABSTRAKKegiatan penelitian ini berlangsung di Kota Bitung, Provinsi Sulawesi Utara dengan kegiatan berpusat di Pelabuhan Perikanan Samudera (PPS) Bitung, yang dimulai dari pertengahan bulan Maret hingga bulan April 2019. Aktivitas perikanan tangkap yang ditelaah berlangsung di sekitar perairan Provinsi Sulawesi Utara yaitu Laut Sulawesi dan Laut Maluku yang masuk ke dalam WPP 715 dan 716 berdasarkan data tangkapan tuna yang didaratkan di PPS Bitung. Tujuan dari penelitian ini adalah untuk menganalisis nilai potensi lestari dengan melihat tingkat pemanfaatan dan maximum sustainable yield (MSY) ikan tuna di sekitar perairan Provinsi Sulawesi Utara berdasarkan pendekatan model produksi surplus (Model Schaefer). Penelitan ini diharapkan dapat digunakan sebagai bahan pertimbangan dalam pengelolaan stok ikan tuna di sekitar perairan Provinsi Sulawesi Utara, serta dapat digunakan sebagai dasar untuk penelitian selanjutnya. Penelitian ini menggunakan metode pengumpulan data sekunder berbentuk dokumen. Data yang diambil adalah data tangkapan ikan tuna dan upaya penangkapan ikan atau effort (trip), dari tahun 2014 sampai dengan 2018 (5 Tahun). Hasil penelitian menunjukkan potensi lestari perikanan tuna di sekitar perairan Provinsi Sulawesi Utara berdasarkan data PPS Bitung Sulawesi Utara nilai potensi lestari tuna yang bisa ditangkap adalah 14.173,51 ton/tahun 80% dari nilai pemanfaatan sumber daya perikanan tangkap tuna di sekitar perairan Provinsi Sulawesi Utara berdasarkan data PPS Bitung yang sebesar 17.716,15 ton/tahun untuk Hmsy, 1.200,15 trip/tahun untuk Emsy, dengan nilai CPUE rata-rata tahun 2014-2018 sebesar 19 ton/trip. Tingkat pemanfaatan tuna di sekitar perairan Provinsi Sulawesi Utara berdasarkan data PPS Bitung Sulawesi Utara di tahun 2014,2017 dan 2018 sudah yang menandakan adanya indikasi overfishing dengan tingkat pemanfaatan terbesar di tahun 2014 yang mencapai nilai 155,09%.Kata Kunci: ikan tuna, Bitung, PPS Bitung, potensi lestari, MSY.